Anti-endothelial cell antibodies in pathogenesis of vasculitis - Zhang, Tian; Li, Liqun; Huang, Shengshi; Starodubtseva, Maria N.; Liu, Ju (Frontiers in Immunology, 2025)
Vasculitis is a group of syndromes characterized by inflammation, presence of autoantibodies and endothelial cells (ECs) damage, which lead to stenosis or occlusion of the vascular lumen. Anti-endothelial cell antibodies (AECAs) are a heterogeneous group of autoantibodies in vasculitis. AECAs bind to antigens and membrane-bound proteins of ECs, inducing inflammation, coagulation, and apoptosis. In this review, we discuss the pathological role of AECAs in different types of vasculitis. In addition, AECAs potentially induce alterations of ECs mechanical properties, and subsequently promotes angiogenic phenotypes in the occurrence of vasculitis.